PENGARUH SERTIFIKASI KOPI TERHADAP CURAHAN TENAGA KERJA DAN STRUKTUR PENDAPATAN RUMAH TANGGA PETANI DI KABUPATEN LAMPUNG BARAT - Hesti Permata Sari; R Hanung Ismono; Zainal Abidin (Lampung University, 2018)
This reseacrh aimed at analyzing the implementation of coffee certification, effect of coffee certification on the use of labor and income structure of coffee farmers. This research was conducted in West Lampung District in which data was collected from November 2016 to February 2017 by survey technique. The samples size in this research were 124 respondents, consisting of certification and non certification farmers. The data was analyzed by implementation of 4C certification, the use of labor, and farm income analysis. The results of the study showed that implementation of coffee certification has not been fully implemented, there was insignificant difference in the use of labor between certification and non certification coffee farmers, and there was insignificant difference in farm income between certification and non certification coffee farmers. The total income of certified and non-certified coffee farmer households were Rp35,724,221 and Rp30,717,102; whereas, contribution of coffee farm income to certified and non certified farmers were 72.62% and 69.28%.Key words : certification, coffee, income, labour